Development of a model system to analyze chondrogenic differentiation of mesenchymal stem cells - Ruede, Anke; Hofmeister, Simone; Bosserhoff, Anja Katrin (International Journal of Clinical and Experimental Pathology, 2013)
High-density cell culture is widely used for the analysis of cartilage development of human mesenchymal stem cells (HMSCs) in vitro. Several cell culture systems, as micromass, pellet culture and alginate culture, are applied by groups in the field to induce chondrogenic differentiation of HMSCs. A draw back of all model systems is the high amount of cells necessary for the experiments. Further, handling of large experimental approaches is difficult due to culturing e.g. in 15 ml tubes. Therefore, we aimed to develop a new model system based on "hanging drop" cultures using 10 to 100 fold less cells. Here, we demonstrate that differentiation of chondrogenic cells was induced as previously shown in other model systems. Real time RT-PCR analysis demonstrated that Collagen type II and MIA/CD-RAP were upregulated during culturing whereas for induction of hypertrophic markers like Collagen type X and AP-2 epsilon treatment with TGF beta was needed. To further test the system, siRNA against Sox9 was used and effects on chondrogenic gene expression were evaluated. In summary, the hanging drop culture system was determined to be a promising tool for in vitro chondrogenic studies.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Chondrogenic differentiation; Collagen; Hanging drop; Human mesenchymal stem cells